GPx3 knockdown inhibits the proliferation and DNA synthesis and enhances the early apoptosis of human spermatogonial stem cells via mediating CXCL10 and cyclin B1 - Wu, Si; Cheng, Zixin; Peng, Ye; Cao, Ying; He, Zuping (Frontiers in Cell and Developmental Biology, 2023)
Spermatogenesis is regulated by genetic and epigenetic factors. However, the genes and signaling pathways mediating human spermatogenesis remain largely unknown. Here, we have for the first time explored the expression, function, and mechanism of glutathione peroxidase 3 (GPx3) in controlling the proliferation and apoptosis of human spermatogonial stem cells (SSCs). We found that GPx3 was expressed in human SSCs. Notably, we revealed that GPx3 knockdown resulted in the decrease in the proliferation, DNA synthesis, and cyclin B1 level in human SSC lines, which possessed the phenotypic features of human primary SSCs. Flow cytometry and TUNEL assays showed that GPx3 silencing led to enhancement of early apoptosis of human SSC line. RNA sequencing was utilized to identify CXCL10 as a target of GPx3 in human SSCs, and notably, both double immunostaining and co-immunoprecipitation (co-IP) demonstrated that there was an association between GPx3 and CXCL10 in these cells. CXCL10-shRNA resulted in the reduction in the proliferation and DNA synthesis of human SSC line and an increase in apoptosis of these cells. Taken together, these results implicate that GPx3 regulates the proliferation, DNA synthesis, and early apoptosis of human SSC line via mediating CXCL10 and cyclin B1. This study, thus, offers a novel insight into the molecular mechanism regulating the fate determinations of human SSCs and human spermatogenesis.